Sleep-disordered breathing in patients on opioids for chronic pain. Issue 10 (13th October 2020) - Selvanathan, Janannii; Peng, Philip W H; Wong, Jean; Ryan, Clodagh M; Chung, Frances
Abstract : The past two decades has seen a substantial rise in the use of opioids for chronic pain, along with opioid-related mortality and adverse effects. A contributor to opioid-associated mortality is the high prevalence of moderate/severe sleep-disordered breathing, including central sleep apnea and obstructive sleep apnea, in patients with chronic pain. Although evidence-based treatments are available for sleep-disordered breathing, patients are not frequently assessed for sleep-disordered breathing in pain clinics. To aid healthcare providers in this area of clinical uncertainty, we present evidence on the interaction between opioids and sleep-disordered breathing, and the prevalence and predictive factors for sleep-disordered breathing in patients on opioids for chronic pain. We provide recommendations on how to evaluate patients on opioids for risk of moderate/severe sleep-disordered breathing in clinical care, which could lead to earlier use of therapeutic interventions for opioid-associated sleep-disordered breathing, such as opioid cessation or positive airway pressure therapy. This would improve quality of life and well-being of patients with chronic pain.